Mina Alaska - Ruiz, Jorge, 1924-2012; Roncal, Hugo, 1923-2005; Wagner, Christa; Sánchez de Lozada, Gonzalo; Botelho Gosálvez, Raúl, 1917-2004 ([Proinca Bolivia], 1968)
Jenny Smith is a young American journalist searching for her long-lost grandfather in the mountains of Bolivia. She enlists the help of her grandfather's partner and fellow gold-prospector, Rodrigo Diaz.